PENTINGNYA PERAN SUPPORT SYSTEM DALAM PERKULIAHAN TERHADAP PROSES BELAJAR - Fauziah, Della Fariha; Mujiburohman, Dian Aries (Universitas Tanjungpura, 2023)
Sekolah Tinggi Pertanahan Nasional (STPN) is an official high school under the auspices of the ATR/BPN Ministry. The educational approach at STPN is based on a semi-military pattern that emphasizes physical and spiritual health, so cadets and cadets become physically stronger. Therefore, the importance of mutual support in the form of a support system is highly emphasized here, because it is able to provide positive energy for one another. This study aims to describe how important calm and comfort are for cadets and cadets in going through the lecture process, especially in the aspect of learning motivation. The existing support system makes them feel protected, so everything feels safe and light. The research method used is a quantitative method, and the results of hypothesis testing show that STPN cadets and cadets need a partner or companion as the best support system on campus. The support system is usually in the form of the opposite sex exchanging stories, complaints, and silly things that increase enthusiasm. With this support system, they have a shoulder to lean on while going about their daily lives in the learning process which may not be effective and conducive. However, the presence of this support system by their side of life makes the days more planned, structured, and coordinated as best they can.